Development of mobile-based point of sales android application for food and drink stalls - DeVera, Trisha Angeline M. (Animo Repository, 2022)
The aim of this thesis is to develop a Point of Sales Android mobile application which focuses on small food and drink businesses to help them improve their business operations with minimal costs. The inclusion of SMS feature for sending sales details offline was the applied solution to achieve this. Also, online features are added for user authentication and backing up of data online. The application was tested on the devices of 20 business participants consisting of owners and employees. System Usability Scale was utilized afterwards as a tool for measuring the system’s usability by letting participants answer the survey form.